Implementation of Religious Character in Developing Religious Values in Early Childhood: A Case Study at TK Negeri Gansal - Rasti Andie; Nurhayati Hamzah; Ika Juhriati (FKIP - Universitas Riau, 2026)
This study investigates the implementation of religious character education in developing religious values among early childhood learners at TK Negeri Gansal, Banggai Kepulauan Regency, Indonesia. Early childhood (0–6 years) is widely recognized as a critical period for establishing moral and spiritual foundations. This study aims to describe the implementation process, evaluate its effectiveness, and identify challenges and solutions in strengthening religious character in daily school activities. This research employed a qualitative case study design. Data were collected through classroom observations, semi-structured interviews with the principal, teachers, and parents, and documentation of learning programs and school activities. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing. The findings show that religious character education was implemented effectively through consistent habituation, including daily prayers before and after activities, religious songs, and teacher role modeling. Most students achieved good to very good development in indicators such as recognizing God’s creations and practicing daily worship routines. Challenges included limited learning media and inconsistent reinforcement at home. Strengthening parent involvement and developing varied learning resources are recommended to sustain children’s religious character development.